2016
DOI: 10.1111/bcpt.12540
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biliary Levels of Arginine and its Methylated Derivatives after Hepatic Ischaemia/Reperfusion

Abstract: Arginine (Arg) can be methylated to form symmetrical dimethylarginine (SDMA) and asymmetrical dimethylarginine (ADMA), the latter an endogenous inhibitor of nitric oxide synthase (NOS). SDMA is excreted in the urine, while ADMA is mainly subjected to degradation in the liver. Arg competes with ADMA and SDMA for cellular transport across cationic aminoacid transporters (CATs). We evaluated the changes in serum, tissue and biliary levels of Arg, citrulline (Cit), ADMA and SDMA and the modifications in CATs after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Biliary LDH was evaluated as previously reported [ 17 ]. ADMA levels in plasma, tissue and bile were evaluated by direct ELISA kit according to the manufacturing procedure (Immundiagnostik AG-Germany) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biliary LDH was evaluated as previously reported [ 17 ]. ADMA levels in plasma, tissue and bile were evaluated by direct ELISA kit according to the manufacturing procedure (Immundiagnostik AG-Germany) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ferrigno et al, have demonstrated the increase of ADMA levels in a BDL model in rats [76]. In contrast ADMA tissues levels were decreased after hepatic ischemia–reperfusion as described by Ferrigno et al [77].…”
Section: Discussionmentioning
confidence: 94%
“…ADMA levels in plasma, tissue and bile were evaluated by direct ELISA kit according to the manufacturing procedure (Immundiagnostik AG-Germany) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that after hepatic I/R damage, biliary ADMA clearance increases, which is associated with changes in CAT-2A and CAT-2B transporters [ 30 ][ 31 ]. In the present study, we evaluated the effects of the FXR agonist OCA on biliary, serum and hepatic levels of ADMA.…”
Section: Introductionmentioning
confidence: 99%